Deep Neck Lifting - Wever, Capi C. (Facial Plastic Surgery, 2024)
Creating tight and durable profile neck results has perhaps become the principal objective of many surgeons. On social media such results are quickly recognized by colleagues and potential clients alike, much more so than “en-face” results. Yet individual patient characteristics play an essential role in determining if such results are technically possible and also dictate which techniques are required to achieve it. In many patients, these techniques involve manipulation of the deeper neck structures and are oriented more laterally than the direct submental region. Each surgeon needs to decide which technique feels proportionate in terms of an individualized risk–benefit analysis.
Keywords: necklift; aging; surgery; facelift